2008
DOI: 10.2535/ofaj.85.107
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evaluation of the human pyramidal tract: Gender and age differences

Abstract: In the past, morphometric research on the nervous system had tended to focus on neuronal somata. Recently, however, research has started on the evaluation of the nervous pathways, especially of the nerve fibers [1][2][3][4][5][6][7][8] . Out of the reasons for this delay may be the lack of reliable methods for the staining of axons with minimum shrinkage. For example, conventional silver impregnation methods may result in extensive axonal shrinkage. It is therefore indispensable to adopt one of the discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In early adolescence, female motor tracts seem to reflect more widespread changes, while males may undergo relatively more microstructural changes in projective and associative fibers (Hervé et al, 2009;Bava et al, 2011;Pangelinan et al, 2016). Histopathologically, an elegant research study showed that in the human lateral pyramidal tract at the cervical level (C5), large-size myelinated axons are more dominant in number in males, while smallsize myelinated axons are found in relatively lager numbers in females, thus possibly suggesting a sex-difference in the transmission of the responses along this tract (Souma et al, 2008). In line with this finding, neurophysiological nomograms differentiated by sex would be needed to detect even subtle changes.…”
Section: Figurementioning
confidence: 99%
“…In early adolescence, female motor tracts seem to reflect more widespread changes, while males may undergo relatively more microstructural changes in projective and associative fibers (Hervé et al, 2009;Bava et al, 2011;Pangelinan et al, 2016). Histopathologically, an elegant research study showed that in the human lateral pyramidal tract at the cervical level (C5), large-size myelinated axons are more dominant in number in males, while smallsize myelinated axons are found in relatively lager numbers in females, thus possibly suggesting a sex-difference in the transmission of the responses along this tract (Souma et al, 2008). In line with this finding, neurophysiological nomograms differentiated by sex would be needed to detect even subtle changes.…”
Section: Figurementioning
confidence: 99%